PELAKSANAAN BANTUAN LANGSUNG TUNAI DANA DESA PANDEMI COVID-19 - Arif Rahman; Yudi Kisworo (Legalita, 2021)
The impact of epidemics of infectious diseases, such as Covid-19, on the lower middle class is very severe. Indeed, due to limited commercial activities, social and economic impacts have an impact on people's welfare, possibly increasing the number of poor people in Indonesia. In the midst of the Covid-19 outbreak, one of the government's actions is to provide Direct Cash Assistance from the Village Fund (BLT-Dana Desa) to economically and socially underprivileged communities to meet their daily needs. The question raised in this study was how to distribute the BLT Village Fund to Cahaya Negeri Villages in order to help them overcome the impact of the Covid-19 outbreak and other challenges. The empirical approach, used in this work, is the next step. We used primary and secondary data from field studies and literature review. While the data analysis used is qualitative analysis, which explains the facts systematically, thoroughly, and structured so that conclusions are easier to draw from the existing problems. Based on the findings of this study, the Village BLT Fund was distributed in two waves in Cahaya Negeri Village. However, due to several inhibiting factors, such as delays in the implementation of distribution from a predetermined schedule, problems with nepotism or the family system, administrative errors and lack of transparency in the implementation of distribution, and potential errors due to lack of socialization. If done, it can be said that the distribution has not been optimal and is not in accordance with applicable regulations. According to the author, villages should be more fair and open in data collection and announcement of the list of potential KPM BLT Village Funds, and the Village Fund BLT program should be more socialized to all Cahaya Negeri Villages.